Line of Sight Characteristics of Novice Physical Therapists in Motion Analysis - YAMADA, Yoichi; HORIMOTO, Yukari; MARUYAMA, Hitoshi (Rigaku ryoho kagaku, 2013)
[Purpose] We measured the line of sight of novice physical therapists, and by analyzing their investigative ability of motion, we tried to develop a skill index. [Subjects and Method] The subjects were 12 fourth-year students of a vocational training school. We showed them a video of a shoulder being raised after surgery for rotator cuff tear, and measured the stopping points before and after disclosing the profile. We also asked them to describe the type of disorder, points for attention, changes in points for attention, and points for attention in motion analysis, and investigated the line of sight characteristics. [Results] One subject answered the disorder type correctly, and there were significant differences between before and after profile disclosure, in the numbers of stopping points at the shoulder joint, the scapula area, and the elbow region. All subjects responded that the shoulder joint and scapula area were points for attention, answers which were in agreement with the measurement results. After disclosure, we determined the stopping points of those who answered that their points for attention had changed, and the number of points had reduced. [Conclusion] We consider that by presenting novices with a simple task, we can focus their sight on the points necessary for analysis, making it possible for them to gather information.